Kafka streams API for developers using Java/Spring Boot 3.X. (Packt Publishing, 2023)
Welcome to the Kafka Streams API video course, where you will dive deep into building powerful Kafka Streams applications. In the first section, you will start by introducing the fundamental concepts and terminologies associated with Kafka Streams development. You will then move on to building a simple Kafka Streams app and testing it locally to gain hands-on experience. Next, you will explore the various operators available in the Kafka Streams API, gaining a solid understanding of how they contribute to building robust streaming applications. You will also delve into the serialization and deserialization process, learning the best approach to creating a generic serializer and deserializer that can be utilized for any type of message. Moving forward, you will take on the exciting task of implementing an order management system for a retail company using Kafka Streams. You will explore error handling mechanisms, KTable and GlobalKTable concepts, and dive into stateful operators and aggregation-related functionalities. Additionally, you will learn about the importance of rekeying records and the use of joins in your application. Continuing your journey, you will learn about writing automated tests for Kafka Streams apps, including unit tests and integration tests using Embedded Kafka. Additionally, you will explore the concept of a grace period and its application in Kafka Streams. Finally, you will learn how to package your Kafka Streams app as an executable and launch it effectively. By the end of this course, you will have a comprehensive understanding of the Kafka Streams API, enabling you to build a wide range of applications using this powerful tool. What You Will Learn Build advanced Kafka Streams applications using Streams API Build Kafka Streams application using high-level DSL Test Kafka Streams using TopologyTestDriver using JUnit5 Test Spring Kafka Streams using EmbeddedKafka and JUnit5 Aggregate multiple events into aggregated events Learn to join multiple streams into one joined stream About The Author Dilip Sundarraj: Dilip Sundarraj is a software engineer who has experience with building software since 2008. He is passionate about learning modern technologies and staying up to date with all the modern technologies, tools, frameworks, and more. He loves to share his knowledge with the world and that is one of the key reasons for him to be in the online teaching industry. He loves interacting with other software developers and believes that this helps him share knowledge and learn from them. During his leisure time, he loves to play cricket, watch movies, and work out in the gym to have a balance between physical and mental strength. Dilip has a YouTube channel named Code with Dilip, where he has been sharing a lot of technical content related to languages, frameworks, best practices, and more.